Economic Implications Of Brucellosis In Bovine - Panchasara, H.H.; Patel, J.S.; Patel , P.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The study highlights the direct and financially accountable economic losses due to brucellosis in bovine. Among 396 cattle and 643 buffaloes screened for brucellosis using i ELISA, 72 (18.18 %) cattle and 76 (11.82 %) buffaloes were found positive. Economic losses accruing due to brucellosis were maximum (86.03 to 86.44 %) due to reduction in milk production followed by treatment cost and loss of calf due to abortion.